Activities of Detective Units in the National Police of Ukraine: Current Status and Perspectives - O. P. Zavorina; O. V. Fomin (Law and Safety)
Ukrainian law enforcement agencies are undergoing a long-term transformation from a system of punitive law enforcement agencies to European-style law enforcement agencies, which should focus on providing services to the population and respecting human rights. One of the areas of the reform was the introduction of the Detective project in the National Police of Ukraine.